2009
DOI: 10.1093/eurpub/ckp173
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood influences on narghile smoking among youth in Beirut

Abstract: The mechanisms of influence of neighbourhoods on health are not clearly understood, but a transactional paradigm seems most fitting with the results found in this research. Interventions to prevent the narghile smoking should address multiple levels of influence; and must be tailored to the particular aspects of neighbourhoods which are influential in the uptake of this behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 30 publications
1
29
1
Order By: Relevance
“…In terms of the factors leading to substance use, most research has found that peer pressure is the most influential force reported by youth (Aguilar, 2006;Afifi, Yeretzian, Rouhana, Nehlawi, & Mack, 2010;Bousman et al, 2005). Factors such as adverse life events (Lee, Storr, Ialongo, & Martins, 2012), feelings of inadequacy and low self-worth (Almquist & Ostberg, 2013), and parental substance use (Van Der Vorst et al, 2013) were also cited by participants in our study as contributing to substance use.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In terms of the factors leading to substance use, most research has found that peer pressure is the most influential force reported by youth (Aguilar, 2006;Afifi, Yeretzian, Rouhana, Nehlawi, & Mack, 2010;Bousman et al, 2005). Factors such as adverse life events (Lee, Storr, Ialongo, & Martins, 2012), feelings of inadequacy and low self-worth (Almquist & Ostberg, 2013), and parental substance use (Van Der Vorst et al, 2013) were also cited by participants in our study as contributing to substance use.…”
Section: Discussionsupporting
confidence: 49%
“…In our focus groups, youth reported the importance of having a home and the fear of their parents and family as a deterrent for substance use; they also reported being beaten by a parent and thrown outside the house as conducive to substance use. Cultural factors must be also taken into account, especially in regions such as the Middle East, where societal tolerance for tobacco smoking, including the permissive use of water pipe smoking in familial and social settings, has been documented (Afifi et al, 2010;Labib et al, 2007;Momtazi & Rawson, 2010;Mzayek et al, 2012;Schuck, Kleinjan, Otten, Engels, & Difranza, 2012) and can contribute to youth experimentation and uptake, as mentioned in our focus groups.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the measures used in the survey were adapted from previous studies on waterpipe use conducted in the United States and in the Eastern Mediterranean Region (Afifi, Yeretzian, Rouhana, Nehlawi, & Mack, 2010;Azab et al, 2010;Dar-Odeh et al, 2010;Mandil et al, 2010;Maziak, Fouad, et al, 2004;Memon et al, 2000;Saade, Warren, Jones, & Mokdad, 2009;Tamim et al, 2003), while others were constructed for the purpose of this study. Items were Likert type and higher scores indicated greater endorsement of the statement, unless otherwise noted.…”
Section: Methodsmentioning
confidence: 99%
“…Because socioeconomic status has been linked with tobacco use in similar populations, we assessed this construct using paternal education and monthly household income (Afifi et al, 2010;Azab et al, 2010;Dar-Odeh et al, 2010;Mandil et al, 2010;Maziak, Fouad, et al, 2004;Memon et al, 2000;Saade et al, 2009;Tamim et al, 2003;Ward et al, 2006). For monthly household income, we asked participants to select the most appropriate category from three choices: 0-500, 501-900, and 901 or more Jordanian Dinar (JD), where 1 JD is equivalent to approximately 1.09 Euros.…”
Section: Demographicsmentioning
confidence: 99%
“…The profile of the school (factual description, socio-economic profile of students, external and internal food school environment) was obtained from the schools' principals to define the school environment. and refute what is being portrayed about nutrition and healthy lifestyle in media, advertising neighborhood and society [9,11,[15][16][17].…”
Section: Instrumentation and Measuresmentioning
confidence: 99%